A Cross‐Sectional Survey to Assess the Migraineur's Medication Decision‐Making Beliefs: Determining When a Migraine Is Triptan‐Worthy. Issue 7 (14th June 2013) - Landy, Stephen H.; Turner, Ira M.; Runken, M. Chris; Lee, Mechele; Sulcs, Ellen; Bell, Christopher F.
<x xml:space="preserve">Abstract</x> Objectives To investigate the factors that influence a migraineur's beliefs regarding oral triptans for the acute treatment of migraines and to provide further insight into patients' decision‐making process when faced with migraine. Methods A multicenter, cross‐sectional, observational study of subjects currently prescribed an oral triptan medication for the acute treatment of migraine headaches. Subjects were recruited from 6 headache clinics and one primary care practice in the United States. Enrolled subjects completed a questionnaire that could be completed either at the site as part of the visit or at home. The questionnaire comprised 27 questions assessing demographic characteristics, migraine history, migraine frequency and severity, and general beliefs about migraine treatments. The study population was stratified into 2 cohorts (Early Treatment and Delayed Treatment) based on how they typically use their oral triptan to treat a typical migraine. Results A total 506 subjects were enrolled in the study, of which 502 were stratified into the Early Treatment cohort (41.2%) and Delayed Treatment cohort (58.8%). Demographic and clinical characteristics were generally similar between the 2 cohorts. In terms of general treatment patterns, there were notable differences between the Delayed and Early Treatment cohorts, with the Delayed Treatment cohort significantly more likely to take an over‐the‐counter (OTC) or non‐triptan medication first (P ≤ .001) and only take a triptan if the OTC or non‐triptan medication did not work (P ≤ .001). Furthermore, 55% of the Delayed Treatment cohort delayed taking a triptan to be certain that the headache was a migraine (vs 32% of the Early Treatment cohort; P ≤ .001). When asked to specify the reasons for delaying treatment with a triptan, the Delayed Treatment cohort had, in general, greater concerns about using their oral triptan in comparison with the Early Treatment cohort. In particular, respondents were primarily concerned with running out of their triptan medication with 35% of the Delayed Treatment cohort expressing this concern compared with 22% of the Early Treatment cohort (P ≤ .001). Statistically significant differences were also noted for concerns about taking medications (P ≤ .001), side effects (P ≤ .05), expense (P ≤ .01), and taking prescription medications (P ≤ .001). Conclusions Results build upon previously published studies and suggest that patient beliefs directly influence how migraineurs manage their migraines and have implications for patient outcomes. Such insights should be used to facilitate physician–patient communication and reinforce the need for patient‐centered care to improve patient outcomes.